2020
DOI: 10.4149/gpb_2019040
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different concentrations of glucose on glucose sensors and GLP-1 secretion in the enteroendocrine cell line STC-1

Abstract: Glucose triggers glucagon-like peptide (GLP)-1 secretion from L cells involving several glucose sensors including sodium-glucose transporter (SGLT)1, glucose transporter (GLUT)2, and sweet taste receptors (STRs). This study investigated the effects of different glucose concentrations on GLP-1 secretion, intracellular concentrations of Ca 2+ and cAMP, glucose uptake, and protein levels of SGLT1, GLUT2, and STRs in STC-1 cells. Low glucose (5.6 mM) increased GLP-1 secretion, intracellular Ca 2+ concentration, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It is a synthetic agonist of peroxisome proliferator activator receptor (PPAR-c) and belongs to thiazolidinediones. Studies have found that the rat pituitary adenoma GH3 cell line highly expresses PPAR-c, while CD147, TGF-β1, and MMP-9 are all factors concerning to the invasiveness of tumors, but there are few studies on the expression of TGZ [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It is a synthetic agonist of peroxisome proliferator activator receptor (PPAR-c) and belongs to thiazolidinediones. Studies have found that the rat pituitary adenoma GH3 cell line highly expresses PPAR-c, while CD147, TGF-β1, and MMP-9 are all factors concerning to the invasiveness of tumors, but there are few studies on the expression of TGZ [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that SGLTs and GLUTs produce active and facilitative effects, respectively. The relative roles of SGLTs and GLUTs in GLP-1 secretion induced by glucose have been investigated in seminal studies using pharmacological and genetic interference with SGLTs and GLUTs ( 23 25 ), suggesting that they were essential for GLP-1 secretion induced by glucose associated with the cAMP and Ca2+ signaling system ( 26 , 27 ). Consistent with studies linking decreased SGLT activity with reduced GLP-1, our study found that GLP-1R and SGLT2 were simultaneously decreased in PDR patients ( 28 ), these data indicated that release of GLP-1in DR might be a process that requires SGLT2-mediated glucose transport in the signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of GLP-1 in glucose metabolism and human feeding behavior has driven the development of animal models such as mice, , chickens, , zebrafish, , and pigs; , however, species-specific differences in the regulation and actions of GLP-1 make the relevance of these animal models to humans unclear. , Ex vivo models, such as isolated intestinal chambers using animal tissue, are a less complex alternative, with advantages of an intact vasculature and paracrine system, but are limited by the loss of tissue viability within a few hours . Consequently, tissue-cultured murine and human tumor cell lines are often used to study GLP-1 production. These models have limitations due to their tumor origins with distinct genetic and metabolic differences from normal human L-cells, for example, altered expression of G-protein receptors and altered hormone processing …”
Section: Introductionmentioning
confidence: 99%